Analysis of spatio-temporal variability of lightning activity and wildfires in Western Siberia during 2016-2021 - Kharyutkina, Elena; Pustovalov, Konstantin N.; Moraru, Evgeniia; Nechepurenko, Olga E. (Atmosphere, 2022)
This research compares the spatial and temporal variability of lightning activity associated with wildfires in several natural geographical zones ofWestern Siberia from 2016–2021. The study was based on the World Wide Lightning Location Network (WWLLN) and The Fire Information for Resource Management System (FIRMS) for the warm (April–October) season. It was revealed that areas of hotspots and lightning activity most often coincide in the southwestern part of the territory (near Khanty-Mansiysk and Tyumen), in the mountain regions (Kuznetsk Alatau, Altai), and in the northern part of Kazakhstan. Maximum values of lightning occur in July for the whole territory of Western Siberia, and maximum values of hotspots occur in April in the central and southern regions of Western Siberia. Despite the largest number of fires in the south of the territory, the probability of ignition from lightning over the whole warm season is higher in the northern parts ofWestern Siberia; it reaches up to 30%. Thus, the revealed lightning–fire association allows us to better understand this process in the region that will be useful in the prediction of the potential fire danger in different natural zones.